Prevalence and causes of visual impairment amongst older adults in a rural area of North India: a cross-sectional study. Issue 3 (17th March 2018) - Malhotra, Sumit; Vashist, Praveen; Kalaivani, Mani; Gupta, Noopur; Senjam, Suraj Singh; Rath, Ramashankar; Gupta, Sanjeev Kumar
Abstract : Objectives: To determine the prevalence, causes and associated factors for visual impairment (VI) in rural population of Jhajjar district, Haryana, north India. Methods: A community-based, cross-sectional study was conducted in two blocks of Jhajjar district. A total of 34 villages were selected using probability proportionate to size sampling method. Adults aged 50 years and above were selected using compact segment cluster sampling approach. Presenting visual acuity using LogMAR E chart was measured along with collection of other demographic details as part of the house-to-house survey. Subjective refraction and torch light examination were performed at a clinic site within the village to ascertain VI and its cause. VI was considered when presenting visual acuity was less than 6/18 in the better eye. Common causes of VI viz uncorrected refractive errors, cataract, central corneal opacity and others were noted by optometrists. Descriptive analysis was undertaken. Multivariate logistic regression analysis was performed for determining associated factors with VI. Results: Out of 2025 enumerated adults, 1690 (83.5%) were examined at the household level and 1575 (78%) completed all study procedures. The prevalence of VI was found to be 24.5% (95% CI 21.1 to 26.3) and blindness was 5% (95% CI 3.9 to 6.1). The most common causes of VI were uncorrected refractive errors (50%) and cataract (37%). The VI in study participants was found to be associated with age, gender, marital and educational status. Conclusions: VI is still a public health problem in rural population of Jhajjar district, Haryana. Provision of spectacles and cataract surgical services are simple interventions to address this issue.